Optimal Gear-Shifting of a Wet-Type Two-Speed Dual-Brake Transmission for an Electric Vehicle - Xinxin Zhao; Jinggang Zhang; Nasser Lashgarian Azad; Senqi Tan; Yuhan Song (Tehnički Vjesnik, 2022)
In improving the efficiency of powertrain systems and ride comfort for electric vehicles (EVs), the transmission model is required to enable more accessible and more straightforward control of such vehicles. In this study, a wet-type, two-speed, dual-brake transmission system, as well as a new electromechanical clutch actuator, is presented for EVs. A new coordinated optimal shifting control strategy is then introduced to avoid sharp jerks during shifting processes in the transmission system. Based on a state-space model of the electromechanical clutch actuator and dual-brake transmission, we develop a linear quadratic regulator strategy by considering ride comfort and sliding friction work to obtain optimal control trajectories of the traction and shifting motors under model-based control. Simulations and bench tests are carried out to verify the performance of the proposed control laws. Results of the proposed coordinated control strategy show that noticeable improvements in terms of vehicle jerk and friction energy loss are achieved compared with an optimal control scheme only for the shifting motor as the input.